Sources of cysteine-based pharmaceutical drugs and their halal aspects in product development - Firdaus, Dzikri Anfasa; Jihad, Fikri Hidayatul; Mursaha, Siti Inayah Majreha (IPB University, 2024)
Indonesia is characterized by the largest Muslim population globally, showing the need for supplements and medicines consumed to be halal (permissible under Islamic law). In this context, cysteine is an essential amino acid crucial for biological functions in humans. It is used as a mucolytic agent to help thin mucus in respiratory diseases, such as bronchitis or chronic obstructive pulmonary disease (COPD). Cysteine also serves as a supplement or an antidote to acetaminophen for detoxification or to counteract paracetamol (acetaminophen) overdose, a commonly used drugs to relieve pain and reduce fever. Therefore, this research aims to comprehensively review sources of cysteine, production, and use in pharmaceuticals. This research also explores the opinions of scholars regarding halal aspects that need to be considered when developing pharmaceutical product containing cysteine. The methods used included searching through references of research obtained from Google Scholar, ScienceDirect, NCBI, Elsevier, the Qur'an, Hadiths, and other Islamic literature sources. The compound structures were visualized using the ChemSketch tool from ACD/Labs. The results showed that mucolytic and acetaminophen drugs, such as acetylcysteine, could be derived from both animal and plant sources through chemical and nonchemical separation processes. As a precursor of acetylcysteine synthesis, the permissibility of cysteine sourced from specific organs, such as pig hair, had different opinions among scholars. However, the prevailing opinions and fatwa tended to depend on prohibition, based on sources, process, and urgency of use.